DEPICTING HISTORICAL ARCHITECTURE IN CONTEMPORARY UZBEK PAINTING: TECHNIQUES AND PEDAGOGICAL IMPLICATIONS - Madaliyeva Rushana Farhod qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article examines how contemporary Uzbek painters depict historical architecture, focusing on artistic techniques, visual composition, and cultural interpretation. The study analyzes the use of perspective, color harmony, symbolism, and spatial organization in artworks that represent monuments and urban heritage. Additionally, the article discusses pedagogical applications for teaching students how to interpret historical architecture creatively while preserving cultural heritage.